Manifestation and Associated Factors of Pregnancy-Related Worries in Expectant Fathers - Göbel, Ariane; Arck, Petra; Hecher, Kurt; Schulte-Markwort, Michael; Diemert, Anke; Mudra, Susanne (Frontiers in Psychiatry, 2020)
Background: During the last decades, fathers have increasingly participated in prenatal care, birth preparation classes and childbirth. However, comparably little is known about the prenatal emotional well-being of fathers, particularly content and extent of broader paternal concerns that may arise during pregnancy beyond those focusing on childbirth. Thus, the aims of this study were investigating the manifestation of paternal pregnancy-related worries in a population-based sample and identifying relevant associated factors. Materials and Method: As part of a longitudinal pregnancy cohort at the University Medical Center Hamburg-Eppendorf, Germany, N=129 expectant fathers were assessed once during pregnancy. Pregnancy-related worries centering around medical procedures, childbirth, health of the baby as well as socioeconomic aspects were assessed with the Cambridge Worry Scale (CWS). Additionally, paternal socioeconomic background and maternal obstetrical history, symptoms of generalized anxiety, depression and level of hostility were investigated, as well as perceived social support. The cross-sectional data was analyzed based on multiple regression analyses. Results: The level of reported worries was overall low. Some fathers reported major worries for individual aspects like the health of a significant other (10.9%) and the baby (10.1%), but also the current financial (6.2%) and employment situation (8.5%). Pregnancy-related worries were negatively associated with household income, and positively associated with anxious and depressive symptoms and low perceived social support. Associations varied for specific pregnancy-related worries. Limitations: Due to the cross-sectional data examined in this study, a causal interpretation of the results is not possible. The sample was rather homogeneous regarding its socioeconomic background. More research needs to be done in larger, more heterogeneous samples. Conclusion: Though overall worries were rather low in this sample, specific major worries could be identified. Hence, addressing those fathers reporting major worries regarding specific aspects already in prenatal care might support their psychosocial adjustment. Fathers with little income, those with elevated levels of general anxious and depressive symptoms, and less social support reported higher pregnancy-related worries. Our results indicate the relevance of concerns beyond health- and birth-related aspects that could be relevant for fathers. Measurements developed specifically for expectant fathers are needed to properly capture their perspective already during pregnancy.